Block pilot based channel estimation and high-accuracy signal detection for GSM-OFDM systems on high-speed railways - Gong, Bo (2019)
In this paper, generalized spatial modulation-orthogonal frequency-division multiplexing is introduced to wireless communication system on high-speed railways for the first time. There are two main challenges to be tackled. On the one hand, channel estimation is difficult as small number of subcarriers are activated; on the other hand, as both the dimensions of the channel matrix and the number of nonzero elements of the unknown signals are large, the matching based and the compressive sensing based signal detectors may not work effectively. To overcome these problems, we first propose a new channel estimation scheme, in which the block pilot pattern instead of the comb pilot pattern is used and a novel interpolation method, which takes the time variation property in different symbols into consideration is adopted. Simulation results demonstrate that in comparison to the conventional interpolation methods, our proposed method achieves better normalized mean square error performance. Then, for the signal detection, we adopt the decomposition and iteration to reduce the dimension of the matrix to be processed. Based on the decomposed structure, the maximum likelihood method is conducted in the solution space to detect the signal. Simulation results demonstrate that the proposed detector presents higher accuracy compared with the existing signal detection schemes.